Occurrence of pre-sunset L-band scintillation due to strong presence of sporadic-E over Arabian Peninsula. Issue 10 (15th May 2020) - Shaikh, M.M.; Fernini, I.; Gopakumar, G.; Alameri, N.M.
Abstract: Rapid fluctuations in the amplitude and phase of L-band GNSS signals occur, when they pass through the ionosphere, because of electron density irregularities. This so-called scintillation is a consequence of electron density irregularities mainly in the E and F regions of the ionosphere. The daytime scintillation is proven to be linked with E-region irregularities by the existence of a cloud of intense sporadic-E (Es ) in the path of radio waves, which produces scintillation even during the daytime at low latitudes. In this study, we have reported the presence of L-band (lower and upper) scintillation observed using data from a newly established GNSS station (SHJ1) situated under the northern crest of the equatorial ionization anomaly (EIA) near Arabian Peninsula at 25.3°N and 55.5°E. The presence of daytime L-band scintillation is found to be consistent with the appearance of Es . A significant presence of weak, moderate and strong scintillation has been observed throughout the day, in general, and in the late afternoon hours (LT 1500–1800), in particular. However, no significant post-sunset and post-midnight scintillation has been observed. The reported pattern of scintillation occurrences over Sharjah differs in many regards to the previous studies, specifically, the local time of peak occurrences. Using RO data, it has been concluded that Es does exist around Sharjah and the occurrence of it appears to be associated with the appearance of scintillation during pre-sunset hours.